2002
DOI: 10.1177/0008068320020512
|View full text |Cite
|
Sign up to set email alerts
|

On the Geometry of Censored Models

Abstract: This paper looks at the process of censoring via the differential geometric theory of Amari (1990) . This theory gives both a conceptual framework and a set of useful tools which help in mastering the asymptotic theory of estimation and testing. After briefly reviewing results from the theory, noting the natural geometry enjoyed by exponential and curved exponential families, the paper examines how censoring can be viewed in a geometric way. In particular the issue of information loss and the sampling properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…It is assumed the random variable Z has an exponential distribution, but only Y = min{Z, t} is observed. As discussed in [17], this gives a one-dimensional curved exponential family inside a two dimensional regular exponential family. Figure 1 shows some of the details of the geometry of the curved exponential family which is created after censoring.…”
Section: Example 1 (Continued)mentioning
confidence: 92%
“…It is assumed the random variable Z has an exponential distribution, but only Y = min{Z, t} is observed. As discussed in [17], this gives a one-dimensional curved exponential family inside a two dimensional regular exponential family. Figure 1 shows some of the details of the geometry of the curved exponential family which is created after censoring.…”
Section: Example 1 (Continued)mentioning
confidence: 92%
“…It is assumed the random variable Z has an exponential distribution but only Y = min{Z, t} is observed. As discussed in [28] this gives a one-dimensional curved exponential family inside a two dimensional regular exponential family of the form…”
Section: Continuity and Compactnessmentioning
confidence: 95%

Computational information geometry: theory and practice

Anaya-Izquierdo,
Critchley,
Marriott
et al. 2012
Preprint
Self Cite
“…It was observed that a censored exponential distribution gives a reasonable, but not exact, fit. As discussed in [11], this gives a one-dimensional curved exponential family inside a two-dimensional regular exponential family of the form:…”
Section: Examplesmentioning
confidence: 99%